Exploring mental health implications of informal caregiving for the older adult within the Hispanic community: an in-depth cross-cultural analysis of depression symptoms - Muñoz-Alicea, Angel; Suarez-Gomez, William (Frontiers in Public Health, 2025)
This study contributes to a deeper understanding of depression among Hispanic informal caregivers of older adults. As aging populations grow across Latin America and the U.S., it is essential to examine how sociocultural and demographic variables influence caregivers' mental health. A non-experimental, cross-cultural design quantitative research was conducted in Colombia, Mexico, and Puerto Rico-countries with strong representation in the U.S. Using the Psych Data platform and the Patient Health Questionnaire-9 (PHQ-9), a total of 1,194 informal caregivers were assessed for self-rated depressive symptoms and perceived social support. Multivariate statistical analyses were conducted using linear regression analyses and t-test to investigate the correlations between the sociodemographic profiles and depression symptoms of caregivers for older adults in primary care by country. The findings highlight associations between informal caregiving and gender, depression, age, education, employment, spirituality, and familism. Results showed that employment was positively associated with depressive symptoms (B = 1.452, p < 0.01), suggesting that work may add strain rather than serve as a buffer. Higher educational attainment appeared protective, potentially by improving access to mental health resources and coping strategies. Unexpectedly, spirituality also emerged as a significant predictor of increased depressive symptoms, challenging previous research that frames spirituality as protective. Considering the escalating population of minority older adults facing health decline, it is necessary to enhance comprehension of how these multidimensional variables influence caregiving. These findings underscore the need to tailor ethnocultural interventions to address caregiver burden and mental health disparities in underserved populations.